Facile Interfacial Synthesis of Densely Spiky Gold Nano-Chestnuts With Full Spectral Absorption for Photothermal Therapy - Wan, Zhiping; Gu, Jinmao; Wang, Yining; Qian, Jun; Zhu, Junle; Chen, Feng; Wang, Haoheng; Chen, Huairui; Luo, Chun (Frontiers in Bioengineering and Biotechnology, 2020)
The gold nanostructure is regarded as the most promising photothermal agent due to strong localized surface plasma resonance (LSPR) effect. Especially, the gold nanostructures with sharp spikes on the surface have higher optical signal enhancement, owing to the sharp tips drastically enhancing the intense nanoantenna effect. However, current approaches for the synthesis of spiky gold nano-structures are either costly, complicated or uncontrollable. Herein we report a novel strategy to synthesize gold nano-chestnuts (SGNCs) with sharp spikes as an excellent photothermal agent. The SGNCs were prepared by a facile one-pot interfacial synthetic method, and their controllable preparation mechanism were acquired. The SGNCs exhibited ideal full-spectrum absorption and showed excellent photothermal effect. They have a photothermal conversion efficiency (η) as high as 52.9%, which is much higher than traditional photothermal agents. The in vitro and in vivo results shows the SGNCs could efficiently ablate the tumor cells. Thus, the SGNCs have great potential in photothermal therapy applied in malignant tumors.